Flame-retardant water-resistant polyether polyurethane elastomer and method for preparing the same
Patent Information
- Application Number
- CN202610763541.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-08-28
AI Technical Summary
但关于反应型阻燃剂对聚醚型聚氨酯水解稳定性影响的研究,目前仍鲜有报道
1.本发明通过原位合成含磷-硼协同结构的DMPB阻燃剂,将其引入聚氨酯弹性体基体,可使材料极限氧指数(LOI)由纯PUE的19.6%提升至32.7%,顺利通过UL-94V-0垂直燃烧测试,燃烧时无明显熔滴、无明火蔓延,从根本上解决传统聚氨酯易燃、易滴落、二次火灾风险高的问题。DMPB可显著抑制烟气与有毒气体释放,材料峰值烟气产生率(pSPR)、总烟气生成量(TSP)与最大烟密度分别降低40.7%、48.5%、87.2%,累积烟密度降低92.7%;同时有效抑制CO等有毒不完全燃烧产物释放,显著提升火灾场景下的人员逃生安全性。燃烧过程中,DMPB诱导聚氨酯基体快速形成连续、致密、高强度的P/B/N协同炭层,可有效阻隔热量、氧气传递与可燃气体逸出;与纯PUE几乎无残炭相比,改性体系800℃残炭量达7.50wt.%,炭层结构完整无明显裂纹,隔热与抑燃能力大幅增强。相较于单纯添加BOX导致力学性能大幅下降,DMPB改性聚氨酯弹性体保持良好拉伸强度,断裂伸长率提升至153.82%,较纯PUE提高约52.3%;同时界面粘接性能更优,平均剥离强度达515.09N/m,较纯PUE提升31.9%,实现阻燃改性与力学性能的良好兼容。
Smart Images

Figure CN122647689A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane elastomer technology, specifically to a flame-retardant and water-resistant polyether-type polyurethane elastomer and its preparation method. Background Technology
[0002] Polyurethane elastomers (PUEs) possess excellent adhesion, elasticity, and weather resistance, making them widely used in automotive exterior components, building joints, and electronic devices. However, polyurethane elastomers are rich in hydrocarbon structures, making them flammable and exhibiting a rapid heat release rate. Furthermore, their molecular chains have relatively weak cross-linking, and their melting temperature is lower than their decomposition temperature, resulting in the production of large amounts of molten droplets when heated or burned. In addition, the isocyanate component in the material decomposes upon heating, and the benzene ring structure increases smoke production and generates nitrogen-containing toxic gases such as hydrogen cyanide, posing a significant fire hazard.
[0003] Meanwhile, improving the hydrolysis resistance of polyurethane is also a critical issue that urgently needs to be addressed. While polyether-based polyurethane exhibits better hydrolysis resistance than polyester-based polyurethane, its long-term performance degradation is not primarily due to the hydrolysis of urethane bonds, but rather to the easy absorption of moisture by hydrophilic polyols. Water molecules entering the material increase hydrogen bond spacing and reduce cohesive energy, triggering microphase separation between soft and hard segments. This ultimately leads to material softening, decreased mechanical properties, and a significant reduction in long-term reliability. Therefore, developing polyether-based polyurethane elastomer materials that combine fire safety and hydrolysis resistance has become an urgent need.
[0004] Halogen-free flame-retardant polyurethane systems have attracted much attention in the industry. Currently, mainstream research systems include nanomaterials, metal hydroxides, intumescent flame retardants, nitrogen-based flame retardants, boron-based flame retardants, and phosphorus-based flame retardants. Among them, phosphorus-based flame retardants have particularly broad application prospects due to their dual role in capturing gas-phase free radicals and charring in the condensed phase. For example, Li et al. prepared a polyurethane-like structural flame retardant (D. Li, L. Liu, Z. Zhang, M. Xu, Y. Xu, L. Qian, An urethane-based phosphonate ester for improving flame retardancy and smoke suppression of thermoplastic polyurethane, Polym. Degrad. Stab. 188 (2021) 109568.). When added at a concentration of 12% (mass fraction), the modified polyurethane achieved a UL-94 V-0 flame retardancy rating with a limiting oxygen index (LOI) of 29.1%. Although this flame-retardant system can significantly reduce the heat release rate, it suffers from the problem of high addition amounts, which can impair material compatibility and mechanical properties.
[0005] Reactive phosphorus-containing flame retardants can be covalently integrated into polymer networks, effectively inhibiting flame retardant migration and improving long-lasting flame retardancy, thus gaining more popularity. Wang et al. synthesized phosphorus-containing intrinsically flame-retardant polyester diols (FRPE), which simultaneously improved the flame retardant and mechanical properties of polyurethane (H. Wang, Q. Liu, X. Zhao, Z. Jin, Synthesis of reactive DOPO-based flame retardant and its application in polyurethaneelastomers, Polym. Degrad. Stab. 183 (2021) 109440.); Yang et al. grafted trifluorobenzene onto the modified polyurethane backbone to prepare self-healing flame-retardant polyurethane (MPUF) (S. Yang, S. Wang, X. Du, Z. Du, X. Cheng, H. Wang, Mechanically robust self-healing and recyclable flame-retarded polyurethane elastomer based on thermoreversible crosslinking network and multiple hydrogen bonds, Chem. Eng. J. 391 (2020) 123544.). When the amount of trifluorobenzene added is 8% (mass fraction), the limiting oxygen index of the material increases to 28.5%, and the tensile strength increases from 6.63 MPa to 27.89 MPa.
[0006] However, most existing research focuses on improving flame retardancy ratings and optimizing mechanical properties. Smoke is a major cause of casualties in fires, but research on the smoke generation characteristics and smoke suppression mechanisms of polyurethane elastomers, whether additive or reactive flame retardant systems, is still relatively scarce; and the presence of ether bonds in the molecular chain of polyether-type polyurethane elastomers further increases the difficulty of smoke suppression.
[0007] Introducing nanosheet fillers into polyurethane elastomer systems is an effective means of smoke suppression. The thermoplastic polyurethane / two-dimensional titanium carbide (TPU / MXene) nanocomposite material prepared by Liu et al. showed a 27.3% reduction in heat release rate and a 43.8% reduction in total smoke production, while also improving the tensile strength and toughness of the material (C. Liu, K. Xu, Y. Shi, J. Wang, S. Ma, Y. Feng, Y. Lv, F. Yang, M. Liu, P. Song, Fire-safe, mechanically strong and tough thermoplastic polyurethane / MXene nanocomposites with exceptional smoke suppression, Mater. Today Phys. 22 (2022) 100607.). The magnesium-iron layered bimetallic hydroxide (MgFe-LDH) prepared by Ren et al. (H. Ren, K. Qing, Y. Chen, Y. Lin, X. Duan, Smokesuppressant in flame retarded thermoplastic polyurethane composites: Synergistic effect and mechanism study, Nano Res. 14 (2021) 3926-3934.) and the copper-doped carbon-based boron composite material (CCu@B) developed by Huang et al. (B. Huang, Y. Geng, H. Zhao, H. Zhang, G. Li, H. Zhang, J. Qu, W. Gong, L. Liu, C. Jiao, W. Liu, X. Chen, Synergistic mechanism of gas phase flame retardant-mechanical reinforcement of thermoplastic polyurethane elastomer / copper borate composite materials, Polym. Degrad. Stab. 241 (2025) 111518.) also showed excellent smoke suppression effects.
[0008] However, single nanosheet fillers suffer from drawbacks such as insufficient self-extinguishing ability and poor dispersibility. Combining them with phosphorus-based flame retardants can improve these issues. However, low filler addition levels are insufficient to improve the limiting oxygen index of the material, while high addition levels significantly increase production costs. Therefore, developing new methods to improve the smoke suppression performance of polyurethane without adding nanosheets is of significant practical importance.
[0009] Long-term stability properties, such as hydrolysis resistance, directly determine the service life of polyurethane elastomers, and related research has been gaining momentum in recent years, with hydrolytic stability being a key research focus. Polyether-type polyurethanes exhibit better hydrolytic resistance than polyester-type polyurethanes, but reducing the hygroscopicity of hydrophilic polyols remains a technical challenge. Currently, methods to improve the water resistance of polyether-type polyurethanes mainly fall into two categories: strengthening the cross-linked network structure and introducing hydrophobic groups. However, research on the influence of reactive flame retardants on the hydrolytic stability of polyether-type polyurethanes is still scarce.
[0010] Therefore, developing a halogen-free, high-efficiency, smoke-suppressing, and mechanically superior flame-retardant polyether-type polyurethane elastomer with water resistance has become an urgent need and an important research direction for the high-performance and functional development of polyurethane materials. Summary of the Invention
[0011] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide a flame-retardant and water-resistant polyether-type polyurethane elastomer and its preparation method. First, a boronoxane intermediate (BOX) is prepared, and then reacted with dimethyl methylphosphonate to prepare a reactive flame retardant DMPB with a boronoxane backbone. This DMPB is then introduced into the polyurethane elastomer as a halogen-free flame retardant. The resulting material has a significantly improved limiting oxygen index, reaching the UL-94 V-0 level, and exhibits outstanding smoke suppression and toxicity reduction effects. It forms a continuous and dense char layer during combustion, possesses excellent mechanical and adhesive properties, is halogen-free and environmentally friendly, and water-resistant and stable, making it suitable for fields with high flame-retardant safety requirements, such as new energy vehicles and electronic component potting.
[0012] The technical solution of this invention is as follows: On one hand, the present invention provides a method for preparing a flame-retardant and water-resistant polyether-type polyurethane elastomer, comprising the following steps: S1 Preparation of cycloboroxane intermediate: 3-APBA was dispersed in toluene, heated to 80-100℃ and refluxed with stirring for 12-14 h; after cooling to room temperature, the precipitate was collected by filtration, washed with toluene to remove residual reactants, and then dried under vacuum to obtain cycloboroxane intermediate BOX; S2 Preparation of reactive flame retardant: Dissolve BOX in DMF to obtain BOX solution; heat DMMP to 100-120℃, and add BOX solution dropwise to DMMP; after the addition is complete, raise the temperature to 160-170℃ and keep it at the temperature for 24-48h; after the reaction is complete, remove the solvent DMF by rotary evaporation to obtain liquid product DMPB. Preparation of flame-retardant polyurethane elastomer S3: Dehydrated polyether polyol is treated at 110-120℃ for 2-3 hours under vacuum to remove residual moisture; after cooling to 50-60℃, isocyanate is added, followed by heating to 75-80℃ and holding for 2-3 hours to obtain isocyanate-terminated polyurethane prepolymer; DMPB is dissolved in DMF and added to the prepolymer and stirred, followed by TMP, and the resulting mixture is stirred before casting; after casting, the sample is degassed under vacuum to remove entrained air bubbles and solvent, and cured to obtain flame-retardant polyurethane elastomer.
[0013] Preferably, in step S1, the vacuum drying temperature is 80-110℃ and the time is 6-12h.
[0014] Preferably, in step S2, the concentration of the BOX solution is 0.4-0.93 mol / L.
[0015] Preferably, in step S2, the mass ratio of BOX to DMMP is 1:(3.3-3.8).
[0016] Preferably, in step S2, the pressure during rotary evaporation is -0.09 to -1 MPa.
[0017] Preferably, in step S3, the polyether polyol is PPG-2000 and the isocyanate is MDI-50, with a mass ratio of 1:(0.65-0.7).
[0018] Preferably, in step S3, the mass ratio of DMPB, TMP and polyether polyol is 1:(0.9-2.3):(6-13.5).
[0019] Preferably, in step S3, the curing temperature is 80-100℃ and the time is 12-24h.
[0020] On the other hand, the present invention provides a flame-retardant and water-resistant polyether polyurethane elastomer, which is prepared by the above-described method for preparing flame-retardant and water-resistant polyether polyurethane elastomer.
[0021] Compared with the prior art, the present invention has the following advantages: 1. This invention synthesizes a phosphorus-boron synergistic structure-containing DMPB flame retardant in situ and introduces it into a polyurethane elastomer matrix. This increases the limiting oxygen index (LOI) of the material from 19.6% of the pure PUE to 32.7%, successfully passing the UL-94V-0 vertical burning test. During combustion, there are no obvious drippings or open flame spread, fundamentally solving the problems of flammability, dripping, and high risk of secondary fire associated with traditional polyurethane. DMPB significantly inhibits the release of smoke and toxic gases, reducing the peak smoke generation rate (pSPR), total smoke production (TSP), and maximum smoke density by 40.7%, 48.5%, and 87.2%, respectively, with a cumulative smoke density reduction of 92.7%. Simultaneously, it effectively inhibits the release of toxic incomplete combustion products such as CO, significantly improving the safety of personnel escaping in fire scenarios. During combustion, DMPB induces the rapid formation of a continuous, dense, and high-strength P / B / N synergistic char layer in the polyurethane matrix, effectively blocking heat and oxygen transfer and the escape of combustible gases. Compared to pure PUE with almost no char residue, the modified system achieves a char residue of 7.50 wt.% at 800℃, with an intact char layer structure and no obvious cracks, significantly enhancing its heat insulation and flame-suppressing capabilities. Compared to the significant decrease in mechanical properties caused by simply adding BOX, DMPB-modified polyurethane elastomer maintains good tensile strength, with an elongation at break increased to 153.82%, approximately 52.3% higher than pure PUE. Simultaneously, it exhibits superior interfacial adhesion, with an average peel strength of 515.09 N / m, 31.9% higher than pure PUE, achieving a good compatibility between flame-retardant modification and mechanical properties.
[0022] 2. This invention employs a halogen-free phosphorus-boron synergistic flame-retardant system, free of halogens, heavy metals, and other restricted substances, fully meeting RoHS, REACH, and other environmental regulations. It releases no corrosive or highly toxic gases during combustion, making it suitable for fields with stringent environmental and safety requirements, such as new energy vehicles, electronic component potting, and rail transportation. The material absorbs water primarily through reversible physical adsorption, and its mass is largely restored after drying, with no significant dissolution or degradation loss. While ensuring high flame-retardant efficiency, it retains the basic water-resistant properties of polyurethane elastomers, meeting the long-term use requirements in humid environments. Attached Figure Description
[0023] Figure 1 The following are the preparation routes of DMPB in Example 1 of this invention (a); FTIR spectra of BOX, DMMP and DMPB (b); XPS C1s (c), N1s (d), B1s (e) and P2p (f) spectra of DMPB; TGA and DTG spectra of DMPB (g); XPS C1s (h) and O1s (i) spectra of polyurethane composite material; XPS N1s (j) of PUE / DMPB8.
[0024] Figure 2The images show digital photographs (a) of PUE, PUE / BOX8, PUE / DMPB4, and PUE / DMPB8 in the UL-94 test; the LOI and UL-94 test results (b) of PUE, PUE / BOX8, PUE / DMPB4, and PUE / DMPB8; and the HRR curves (c) and THR curves (d) of PUE, PUE / BOX8, and PUE / DMPB8.
[0025] Figure 3 The pSPR (a), TSP (b), COP (c), CO2P (d), and smoke density (e) curves of PUE, PUE / BOX8, and PUE / DMPB8, and (f) smoke density characteristic data of PUE composite materials.
[0026] Figure 4 The TG curves (a) and DTG curves (b) of PUE, PUE / BOX8, PUE / DMPB4 and PUE / DMPB8 are shown; the three-dimensional TG-FTIR spectra of PUE (c), PUE / BOX8 (d) and PUE / DMPB8 (e) are shown; the absorbance of the pyrolysis products of PUE, PUE / BOX8 and PUE / DMPB8 are shown: isocyanate (f), aromatic compounds (g), ethers (h), carbon dioxide (i), hydrocarbons (j), and hydrogen cyanide (k).
[0027] Figure 5 Digital photographs (a) of PUE, PUE / BOX8, and PUE / DMPB8 at different heating temperatures in a muffle furnace; FTIR spectra of the pyrolysis products of PUE (b), PUE / BOX8 (c), and PUE / DMPB8 (d) at different heating temperatures in a muffle furnace; SEM micrographs of the coke layers inside PUE (e), PUE / BOX8 (f), PUE / DMPB8 (g), and PUE / DMPB8 (h); XPS C1s (i), N1s (j), B1s (k), and P2p (l) spectra of the carbon layer of the polyurethane composite material.
[0028] Figure 6 These are test graphs of the stress-strain curves (a), tensile strength and elongation at break (b), average peel force and average peel strength (c), loss factor (d), loss modulus (e), and energy storage modulus (f) of PUE, PUE / BOX8, and PUE / DMPB8.
[0029] Figure 7The following are the water contact angle test diagrams for PUE, PUE / BOX8, and PUE / DMPB8 (a); actual photos of PUE, PUE / BOX8, and PUE / DMPB8 samples immersed in deionized water (b); stress-strain curves corresponding to PUE (c), PUE / BOX8 (d), and PUE / DMPB8 (e); average peel force and average peel strength test diagrams for PUE, PUE / BOX8, and PUE / DMPB8 (f); LOI test diagrams for PUE, PUE / BOX8, and PUE / DMPB8 (g); UL-94 flame retardancy rating test diagrams for PUE, PUE / BOX8, and PUE / DMPB8 samples in dry state, after immersion in deionized water for 24 h and 48 h and then dried to constant weight (h); and a schematic diagram of the hydrophobic mechanism of DMPB (i). Detailed Implementation
[0030] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention.
[0031] Some of the raw materials used in the examples are from the following sources: 4,4′-Diphenylmethane diisocyanate (MDI-50), polypropylene glycol (PPG-2000), Wanhua Chemical Group Co., Ltd., China.
[0032] Dimethyl methylphosphonate (DMMP, 98%), 3-aminophenylboronic acid (3-APBA, 98%), trimethylolpropane (TMP, 98%) and N,N-dimethylformamide (DMF, AR), Maclean Biochemical Co., Ltd., China.
[0033] Toluene (AR), Tianjin Fuyu Fine Chemical Co., Ltd.
[0034] Example 1 The preparation method of the flame-retardant and water-resistant polyether polyurethane elastomer in this embodiment includes the following steps: S1 Preparation of cycloboroxane intermediates 3-APBA (5 g, 0.037 mol) was dispersed in toluene (50 mL) in a round-bottom flask equipped with a reflux condenser. The mixture was heated to 80 °C and refluxed with stirring for 12 h. After cooling to room temperature, the precipitate was collected by filtration, washed three times with toluene to remove residual reactants, and then dried in a vacuum oven at 80 °C for 6 h to obtain a white solid product, named BOX.
[0035] S2 Preparation of Phosphorus Boroxane BOX (2.3 g, 0.0064 mol) was dissolved in DMF (10 mL) to obtain a BOX solution. Then, DMMP (7.8 g, 0.063 mol) was added to a three-necked round-bottom flask equipped with a condenser and mechanical stirrer, and the system was heated to 120 °C. Next, the BOX solution was added dropwise to the flask. After the addition was complete, the reaction temperature was gradually increased to 170 °C and maintained for 24 h. After the reaction was complete, the solvent was removed using a rotary evaporator at -1 MPa pressure to obtain the liquid product DMPB.
[0036] S3 Preparation of Flame-Retardant Polyurethane Elastomers First, 16.24 g of dehydrated PPG-2000 was added to a three-necked flask and placed under vacuum at 110 °C for 2 h to remove residual moisture. After the temperature dropped to 50 °C, 11.016 g of MDI-50 was added, and the mixture was then heated to 75 °C and reacted for 2 h to obtain an isocyanate-terminated polyurethane prepolymer.
[0037] For pure polyurethane elastomer (PUE), TMP (3.024 g, 0.0225 mol) was added directly to the prepolymer, and the mixture was stirred for 1 min before casting. For polyurethane elastomer containing BOX (PUE / BOX8), TMP (2.07 g, 0.0154 mol) was first introduced into the prepolymer and mixed for 1 min, followed by the addition of BOX (2.55 g, 0.0071 mol), and stirring was continued for 30 s before pouring into a preheated mold. For polyurethane elastomer containing DMPB (PUE / DMPB8), DMPB (2.59 g, 0.0041 mol) was dissolved in DMF (2 mL) and added to the prepolymer and stirred for 30 min, followed by the addition of TMP (2.48 g, 0.0185 mol), and the mixture was stirred for 1 min before casting.
[0038] All cast samples were degassed under vacuum to remove entrained air bubbles and solvent, and cured at 80°C for 12 hours to obtain the final polyurethane elastomer. The samples were labeled PUE, PUE / BOXx, and PUE / DMPBx, respectively, where x represents the loading level.
[0039] Performance characterization and testing methods: Fourier transform infrared (FTIR) spectra of polyurethane elastomers and their residues in the range of 4000-400 cm⁻¹ -1 Recordings were performed using a Nicoleti S10 spectrometer within the specified range.
[0040] Thermogravimetric analysis (TGA) was performed on a Mettler TGA / SDTA851 analyzer at a nitrogen flow rate of 20 mL / min and a heating rate of 10 °C / min from 50 °C to 800 °C. Thermogravimetric-infrared (TG-IR) analysis was performed using a PerkinElmer STA4000-SP3 instrument under the same temperature and gas flow rate (20 mL / min N2). The sample weight used in the tests was 3–5 mg.
[0041] Vertical burning (UL-94) testing was conducted using a CZF-2 instrument (Jiangning Analytical Instruments Co., Ltd., China) according to ASTM D3801-1996 standard, with a sample size of 130mm × 13mm × 3.2mm. Limiting oxygen index (LOI) values were determined using a JF-3 oxygen indexer (Jiangning, China) according to ASTM D2863 standard, with a sample size of 130mm × 6.5mm × 3.2mm. Each flame retardant performance evaluation was performed at least five times.
[0042] The cone calorimeter (CCT) experiment was conducted on a cone calorimeter (West Sussex, UK) at a heat flux density of 35 kW / m³. 2 The sample size is 100mm × 100mm × 4mm, and each sample group is tested three times. Each sample is tested at least three times to obtain the average value.
[0043] Smoke density testing was conducted using a smoke density meter (MotisFireTechnology Co., Ltd., China) in accordance with ISO5659-2:2017 standard, and the corresponding smoke density-time curves were recorded.
[0044] In condensed phase analysis, square samples (1 cm × 1 cm) were placed in a muffle furnace and heated at a selected temperature (300 °C to 600 °C) for 5 min at each temperature. The resulting residues were collected for subsequent FTIR analysis.
[0045] The morphology of the coke residue after combustion was observed using a Regulus 8100 scanning electron microscope (SEM). The surface chemical composition of the coke residue was further analyzed using X-ray photoelectron spectroscopy (XPS) on a Thermo Fisher K-Alpha instrument.
[0046] Mechanical property tests were conducted using an RGT-20A universal testing machine (Shenzhen, China) at 25℃ with a beam speed of 200 mm / min. Five specimens were tested for each group of samples, and the average value was reported.
[0047] The water contact angle was measured using a YIKE-360A contact angle analyzer. The water absorption assessment method involved immersing the sample in deionized water at 35°C for 24 hours. After immersion, the sample was removed, surface moisture was wiped off, and the mass value was recorded. The immersed sample was then dried for 48 hours and weighed again to assess the reversibility of the water absorption process. Several tests were also conducted on the sample, including mechanical property testing, limiting oxygen index testing, and vertical burning testing.
[0048] Performance characterization and test results: (1) Chemical structure characterization In the FTIR spectrum of BOX ( Figure 1 b) The stretching vibrations of amino groups appear at 3325 and 3395 cm⁻¹. -1 At 1340cm -1 The absorption band at 764 cm⁻¹ is attributed to the BO vibration. Furthermore, at 764 cm⁻¹... -1 and 714cm -1 The characteristic vibrations of the B3O3 ring observed at 1244 cm⁻¹ indicate the successful synthesis of BOX. For the starting material DMMP, 1244 cm⁻¹... -1 and 1032cm -1 Characteristic absorption peaks containing phosphorus were observed at 754 cm⁻¹, attributed to the P=O and POC vibrations, respectively. After the reaction of DMMP with BOX, the characteristic peak of the amino group in the DMPB spectrum disappeared, indicating that the primary amine group participated in the reaction. Simultaneously, at 754 cm⁻¹... -1 and 719cm -1 The characteristic absorption peak of the B3O3 ring at 1313 cm⁻¹ and the characteristic absorption peak of the B3O3 ring at 1313 cm⁻¹ -1 The BO absorption band at 1198 cm⁻¹ was preserved. -1 and 985cm -1 The phosphorus-related absorption peak at the point also remained unchanged. This indicates that the phosphorus-containing group has been successfully introduced into the BOX precursor without disrupting the core structure of the cycloboroxane butane.
[0049] XPS was further used to analyze the elemental composition and surface chemical environment of DMPB (e.g., Figure 1 (As shown in (c)-(f)). After peak splitting, the C1s energy spectrum shows four distinct characteristic peaks at 284.4 eV, 284.8 eV, 285.8 eV, and 286.35 eV, corresponding to CB, CC / C=C / CH, CN / CP, and CO bonds, respectively. Figure 1 As shown in (d), the N1s energy spectrum exhibits a characteristic peak at 402.4 eV, which is attributed to the NP bond. The characteristic peak of the high-resolution B1s energy spectrum matches the boron chemical environment corresponding to the BC and BOB bonds, indicating that the cycloboroxane-related structures are preserved after synthesis. Figure 1e). Furthermore, the P2p spectrum can be decomposed into four peaks (133.1 eV, 133.5 eV, 133.9 eV, and 134.6 eV), corresponding to PO, PN, P=O, and PC bonds, respectively. Overall, the results indicate that this DMPB has been successfully synthesized.
[0050] The thermal behavior of DMPB was studied using TGA and DTG (e.g., Figure 1 (g) shows that DMPB exhibits a multi-step decomposition process, with its T... 5% The temperature was 226.7℃, indicating that it could decompose before the PUE decomposes. At the same time, the coke residue reached 33.72 wt.% at 800℃, indicating that it has a strong intrinsic coke-forming ability.
[0051] The chemical structure of polyurethane elastomers was characterized using XPS. Figure 1 h-1j). Comparison with the high-resolution C1s energy dispersive spectroscopy of polyurethane elastomers (h-1j). Figure 1 h) indicates that the peak area attributable to CN bonds with a binding energy of 285.2 eV in the sample is larger than that of pure polyurethane elastomer; simultaneously, a characteristic peak at a binding energy of 532.25 eV, corresponding to BO bonds, was detected. Figure 1 i), proving that BOX and MDI-50 reacted effectively. In the high-resolution C1s energy spectrum of the PUE / DMPB8 composite material, a characteristic peak of the COP bond with a binding energy of 285.6 eV appeared (i). Figure 1 h); its high-resolution N1s energy spectrum also detected an NP bond characteristic peak with a binding energy of 401.7 eV (h); Figure 1 j). This confirms that the two flame retardants, BOX and DMPB, are not simply physical dopants, but have been successfully grafted into the molecular structure of polyurethane elastomers.
[0052] (2) Fire safety analysis of PUE / BOX and PUE / DMPB composite materials To investigate the influence of the chemical structures of BOX and DMPB on the flame retardant properties of PUE, UL-94 vertical burning tests and limiting oxygen index (LOI) tests were conducted on all PUE composite materials. The test results are as follows: Figure 2(a) and 2(b). Pure PUE exhibits high flammability, with an LOI value of only 19.6%, and severe dripping is observed during combustion. The dripping easily ignites absorbent cotton fibers, indicating a significant secondary fire hazard. When 8 wt.% BOX was introduced into the polymer network, the LOI value slightly increased to 23.8%, but the sample still failed to meet the UL-94 standard due to persistent severe flame dripping. This result indicates that, under current conditions, using BOX alone is insufficient to effectively suppress dripping and maintain self-extinguishing properties. In contrast, the addition of DMPB significantly improved the flame retardant properties of the PUE composite: as the DMPB addition increased from 4 wt.% to 8 wt.%, the LOI value further increased from 26.3% to 32.7%, with only PUE / DMPB8 reaching the UL-94 V-0 rating. Furthermore, PUE / DMPB8 rapidly extinguished the flame after ignition, and flame dripping was significantly reduced, indicating a significant improvement in combustion behavior and an effective reduction in the risk of secondary ignition.
[0053] To further assess the combustion hazard of the samples under more realistic fire scenarios, the study employed cone calorimetry (CCT). The test results are as follows: Figure 2 As shown in (c) and 2(d), as shown in Table 1, the ignition time (TTI) of PUE / BOX8 is shorter than that of pure PUE, while the TTI of PUE / DMPB8 (46s) is significantly longer than that of PUE / BOX8 (33s), indicating that BOX and DMPB have different effects on the ignition process and subsequent combustion behavior of PUE. Pure PUE burns violently after ignition, with a peak heat release rate (pHRR) of 995.49 kW / m³. 2 The total heat release (THR) is 110.52 MJ / m³. 2 Adding BOX only produced limited improvement in exothermic behavior, while DMPB showed a more significant inhibitory effect. The pHRR and THR of PUE / DMPB8 decreased to 551.45 kW / m³. 2 and 60.51MJ / m 2 Compared to pure PUE, these figures represent reductions of 44.6% and 45.3%, respectively. The fire safety of PUE is typically assessed using the Fire Spread Index (FGI), Flame Performance Index (FPI), and Flame Retardancy Index (FRI). The Flame Performance Index (FPI) ranges from 0.0392 s·m. 2 / kW increased to 0.0834s·m 2 / kW, Fire Spread Index (FGI) from 4.8799kW / m 2 •s decreased to 2.6012kW / m 2The flame retardancy index (FRI) increased significantly to 3.89. These results collectively demonstrate that PUE / DMPB8 not only effectively delays the ignition process but also significantly inhibits subsequent fire spread and exothermic behavior, thereby greatly improving the overall fire safety of PUE.
[0054] Table 1 Combustion parameters of PUE samples
[0055] Note: a: Ignition time; b: Peak heat release rate; c: Total heat release; d: Fire resistance index; e: Fire spread index; f: Flame retardant index; g: Peak smoke generation rate; h: Total smoke generation.
[0056] In addition to reducing flammability and heat release, DMPB also gives PUE excellent smoke suppression performance, such as... Figure 3 As shown in (a)-3(f), the peak flue gas generation rate (pSPR) of PUE / DMPB8 is reduced from 0.07777m compared to pure PUE. 2 / s decreased to 0.04616m 2 / s, while the total flue gas production (TSP) increased from 10.41m³ / s. 2 Reduced to 5.36m 2 Throughout the combustion process, the CO production (COP) of PUE / DMPB8 remained consistently lower than that of pure PUE, indicating that the release of incomplete combustion products was significantly suppressed. Simultaneously, the CO2 (CO2P) generation also decreased significantly throughout the combustion process, demonstrating that DMPB effectively reduces the release of complete oxidation products. More importantly, smoke density tests showed a further significant reduction in smoke hazard, such as... Figure 3 As shown in (d) and 3(e), the maximum smoke density (Ds,max) of PUE / DMPB8 decreased sharply from 10834.5 in pure PUE to 1390.8, a reduction of 87.2%. Furthermore, the cumulative smoke density over the entire test period (0-239s) decreased from 2076648.0 to 151701.0, a reduction of 92.7%. These results indicate that DMPB not only suppresses instantaneous smoke bursts during combustion but also significantly reduces the cumulative smoke release hazard throughout the combustion process. In contrast, although BOX also reduces smoke release to some extent, its smoke-related parameters are still much higher than those of PUE / DMPB8. Overall, the advantage of DMPB lies not only in improving flame retardant performance but also significantly in simultaneously reducing thermal and smoke hazards. This makes PUE / DMPB8 exhibit the most comprehensive fire safety characteristics among all tested samples, making it the optimal formulation.
[0057] (3) Analysis of gas-phase products and study of pyrolysis behavior The thermal decomposition behavior of PUE and its composites was studied using TGA, such as Figure 4 As shown in (a) and 4(b), the TGA / DTG results (Table 2) show that PUE exhibits typical multi-step thermal degradation behavior of polyurethane, in which hard segments decompose earlier than soft segments. The TGA / DTG results for pure PUE are shown in (a) and (b). 5% The temperature was 311.20℃, T max The thermal response temperature is 405.12℃, and only 0.13wt.% char residue remains at 800℃. After introducing the flame-retardant structure, the thermal response temperature shifts to a lower range: PUE / BOX8's T... 5% The temperature was 277.56℃, T max The decomposition initiation temperature was 396.60℃; while the decomposition initiation temperatures of PUE / DMPB4 and PUE / DMPB8 were even lower, T 5% The values were 244.25℃ and 240.76℃, respectively, and the T value of PUE / DMPB8 was... max The temperature was further reduced to 381.23℃. These results indicate that DMPB does not improve the thermal stability of PUE solely by delaying decomposition, but rather tends to alter the decomposition pathway and induce an earlier thermal response. Notably, although PUE / BOX8 produced the highest amount of char residue at 800℃, its flame retardancy and smoke suppression performance were still inferior to PUE / DMPB8, which retained only 7.50 wt.% char residue. This comparison suggests that the improvement in fire safety performance in the current system cannot be solely attributed to the final char residue yield, but is more closely related to the decomposition pathway and the effectiveness of the protective structure formed during pyrolysis.
[0058] To compare the differences in thermal response between pure PUE and its composites during the main weight loss stages, the Coats-Redfern integral method was used to perform apparent kinetic analysis on the thermogravimetric test data. If the thermal decomposition process is approximated by a first-order kinetic model, the Coats-Redfern equation is expressed as follows:
[0059] In this formula, β is the heating rate, E is the activation energy, R is the gas constant, A is the pre-exponential factor, α is the conversion rate, and T is the thermodynamic temperature (Kelvin).
[0060] Assuming that E is much greater than 2RT, 1-2RT / E is approximately equal to 1. For ease of linear fitting, this study adopts the following definition:
[0061] Subsequently, it was concluded that According to the formula The apparent activation energy was calculated from the slope. This invention selected data from the 0.10 ≤ α ≤ 0.80 interval during thermal decomposition for linear fitting to reduce interference. The fitted linear equations and activation energies E are summarized in Table 3. The apparent kinetic results obtained by the Coats-Redfern method serve only as supplementary evidence for the main mass loss stage. PUE / DMPB8 exhibits a lower apparent activation energy than pure PUE, consistent with its early thermal response behavior.
[0062] To further elucidate the influence of DMPB on the pyrolysis behavior of PUE, TG-FTIR was used to monitor the evolution of pyrolysis products. Three-dimensional TG-FTIR spectra ( Figure 4 (c)-4(e) show that the gaseous products released during the pyrolysis of PUE and its composites are basically similar, indicating that the addition of BOX or DMPB mainly changes the release intensity and temperature distribution of pyrolysis products. The thermal decomposition of pure PUE mainly produces ethers (1108 cm⁻¹). -1 ), aromatic compounds (1510cm) -1 ), carbonyl (1734cm) -1 ), carbon dioxide (2360cm) -1 Hydrocarbons (2977cm) -1 Add water. After adding BOX, at 1419cm -1 A characteristic BO peak appears at 1269-1274 cm⁻¹; after introducing DMPB, peaks appear at 1269-1274 cm⁻¹. -1 and 978-980cm -1 The presence of characteristic peaks attributable to P=O and POC in the region indicates that phosphorus-containing structures are involved in the pyrolysis process. For clearer comparison, several representative bands were further selected to analyze their evolution behavior. For the PUE / DMPB8 system, 2275 cm⁻¹... -1 The NCO-related spectral bands at the location were significantly weakened (e.g. Figure 4 (f) shows that the release of the isocyanate intermediate mainly originates from the effective inhibition of the hard segment; 1510cm -1 The overall evolution intensity of aromatic-related spectral bands also decreased (e.g. Figure 4 (g) shows that the formation of nitrogen-containing aromatic fragments that easily generate fumes is effectively suppressed. Similarly, the 1100 cm⁻¹ of volatile ether products... -1 The intensity of the spectral bands decreased after the introduction of DMPB (e.g. Figure 4 As shown in (h), this indicates a reduction in the release of oxygen-containing fragments originating from the soft chain. In contrast, the performance of PUE / BOX8 typically falls between that of pure PUE and PUE / DMPB8.
[0063] In addition, PUE / DMPB8 is at 2360cm -1 The carbon dioxide absorption peak appears earlier at (e.g.) Figure 4 (i) shows that the intensity of its main release process is lower than that of pure PUE. 2977cm -1 The hydrocarbon absorption peaks at these locations reflect the release of combustible volatile organic fragments (such as hydrocarbons) during pyrolysis. Figure 4 (j) shows that HCN is a toxic gas produced during the material decomposition process (such as...). Figure 4 (k) shows that, compared with the pure sample, the absorption peak intensities of hydrocarbons and HCN decreased significantly after the addition of DMPB. This indicates that the incorporation of this substance can reduce the release of combustible gases and smoke precursors in the gas phase and promote the release of carbon dioxide in the early stage of material degradation.
[0064] Combined with the TGA results, these observations indicate that DMPB does not simply delay the thermal decomposition process of PUE, but rather alters its pyrolysis pathway, causing it to proceed through an earlier but milder volatilization process. Therefore, the release of combustible gases and smoke precursors into the gas phase is effectively reduced, consistent with the significant improvement in the flame retardancy and smoke suppression performance of PUE / DMPB8 observed in the previous section.
[0065] Table 2. TGA data for PUE, PUE / BOX8, PUE / DMPB4, and PUE / DMPB8 samples.
[0066] Note: a: Temperature corresponding to 5% weight loss; b: Temperature corresponding to 50% weight loss; c: Temperature corresponding to the maximum weight loss rate.
[0067] Table 3 Combustion characteristic parameters of PUE samples
[0068] Note: a: Linear fitting equation in the Coats-Redfern method; b: Apparent activation energy.
[0069] (4) Condensed phase analysis To elucidate the condensed phase evolution process of different polyurethane systems and the smoke suppression mechanism of DMPB, the transformation process of the elastomer to the post-combustion char layer was studied using a staged muffle furnace treatment, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). Muffle furnace images obtained at 300-400℃ show that the thermal response of all composite systems is earlier than that of pure PUE (e.g., ...). Figure 5(as shown in (a)). When the temperature rises to 500°C, PUE and its composites begin to form a carbon layer. At 600°C, PUE / DMPB8 still maintains a maximum and continuous carbon layer structure, while pure PUE almost loses its carbon layer due to severe collapse. These results indicate that DMPB-containing elastomers can more effectively promote early condensed phase solidification and structural retention during thermal decomposition.
[0070] The FTIR results further support this macroscopic evolutionary trend (e.g. Figure 5 (b)-5(d) are shown). For pure PUE (as shown in the figure), Figure 5 (b) shows the aliphatic CH stretching vibration region (3000-2800 cm). -1 Carbonyl-containing regions (1720-1680 cm⁻¹) -1 ) and 1096cm -1 The ether skeleton band at 300℃ remained clearly visible, but rapidly decayed in the 400-600℃ range, indicating that the original polyurethane skeleton was continuously consumed and failed to be effectively converted into structurally stable high-temperature carbon. In contrast, PUE / BOX8 showed a clearer band in the aromatic region (1600-1500 cm⁻¹). -1 ) and 827cm -1 Characteristic peaks are still retained in the nearby borooxane-related regions (such as...) Figure 5 (c) shows that PUE / DMPB8 is between 1260-1180cm. -1 The interval further retains regions containing phosphorus groups (such as...) Figure 5 (d) shows that DMPB not only promotes the early solidification process of condensed phase, but also promotes the formation of thermal stability of phosphorus-containing carbon structures.
[0071] Combining the final char residue from thermogravimetric analysis (TGA) with scanning electron microscopy (SEM) observations (such as... Figure 5 As shown in (e)-5(h), it can be clearly determined that the key factor determining flame retardant performance and smoke suppression effect is not the char layer yield itself, but the char layer quality. The char layer structure of pure PUE is loose, fragile, and densely defective, making it difficult to form an effective barrier (e.g., ...). Figure 5 (e) As shown. Although PUE / BOX8 has demonstrated strong carbonization ability, its residue still exhibits obvious cracks and lacks the continuity required to construct an efficient protective barrier (e.g., Figure 5 (f) shows that, in contrast, the outer carbon layer formed by PUE / DMPB8 is the smoothest and most continuous, with significantly fewer cracks; its inner carbon layer exhibits a thicker cell wall and buffer cavity structure, rather than a fragile hollow foam morphology (as shown in f). Figure 5(as shown in 5(g) and 5(h)). This microstructure is more conducive to simultaneously blocking heat and oxygen penetration and inhibiting the outward diffusion of combustible decomposition products. Therefore, PUE / DMPB8 is superior to PUE / BOX8 not because of its higher residual content, but because it constructs a more efficient condensed phase barrier structure.
[0072] XPS provides direct chemical evidence for the formation of high-quality carbon layers (e.g., Figure 5 (i)-5(l) are shown). Before combustion, the carbon XPS results showed that, compared with pure PUE, the relative integrated area of the CC bond in the C1s spectra of PUE / BOX8 and PUE / DMPB8 was reduced, while the CN / CB, CN / CP, and CO and C=O components became more significant (e.g. Figure 5 (i) shows that some intermediates, which would normally enter the gas phase as oxygen- / nitrogen-containing pyrolysis fragments, were not released directly but were reorganized and fixed on the condensed carbon surface. N1s spectra further revealed that nitrogen in pure PUE carbon mainly exists in the form of pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen, while PUE / BOX8 and PUE / DMPB8 also exhibited high-binding-energy oxidized / quaternary nitrogen, indicating that the modified system is more conducive to retaining and stabilizing potential nitrogen-containing smoke precursors (such as...) on the carbon surface. Figure 5 (j) shows that, at the same time, the B1s spectrum of PUE / BOX8 is dominated by BO bonds, indicating that boron is mainly retained in the condensed phase in the oxidized form after combustion (e.g., Figure 5 (k) shows that, in contrast, the integrated area of BC and BN bonds in PUE / DMPB8 is increased, suggesting that boron is further integrated into the carbon-nitrogen framework structure. More importantly, the P2p spectrum of PUE / DMPB8 contains PC, PN, PO, and P=O bonds, with PN and PC bonds being dominant. This indicates that phosphorus remains in the condensed phase within the phosphorus oxide-containing structure and maintains chemical bonding with the carbon-nitrogen framework, jointly constructing the carbon layer structure (as shown in k). Figure 5 (l) shows that the results indicate that PUE / DMPB8 ultimately forms a P / B / N carbon layer structure with a synergistic coupling effect. This structure not only improves the continuity and stability of the carbon layer, but also more effectively immobilizes oxygen- and nitrogen-containing pyrolysis products—substances that, if not immobilized, would enter the gas phase and participate in smoke generation, thus giving the system excellent smoke suppression performance. During the pyrolysis of polyurethane, a large amount of oxygen-, nitrogen-, and aromatic volatiles are generated. These substances are important precursors to smoke, therefore, immobilizing them in the condensed phase has direct significance for smoke suppression.
[0073] (5) Mechanical properties The mechanical properties of the material were analyzed, and the results are as follows: Figure 6 As shown. By Figure 6As shown in (a) and (b), the tensile strength of pure polyurethane elastomer is 22.45 MPa, and the elongation at break is 101.02%. After incorporating BOX, the tensile strength of PUE / BOX8 decreases to 12.45 MPa, while the elongation at break reaches 115.83%. In comparison, the tensile strength of PUE / DMPB8 is 14.72 MPa, higher than that of the PUE / BOX8 composite, and its elongation at break increases to 153.82%. This indicates that DMPB can intercalate between the polyurethane elastomer molecular chains, increasing the free volume and spacing between molecular chain segments. Figure 6 As shown in (c), the average peel strength of pure PUE is 390.67 N / m. After adding BOX and DMPB respectively, the peel strength of the materials increased to 491.01 N / m and 515.09 N / m, respectively. Compared to pure PUE, the average peel strength of the PUE / BOX8 and PUE / DMPB8 composites increased by approximately 25.7% and 31.9%, respectively. This is because DMPB increases the free volume between polyurethane elastomer chain segments, enhancing the mobility of the molecular chains. The improved flowability allows the polyurethane elastomer to more easily penetrate the micropores and rough structures on the substrate surface, forming more physical anchoring points, and thus strengthening the intermolecular forces.
[0074] By employing dynamic mechanical-thermal analysis, the macroscopic properties of materials are explained from the perspective of molecular chain segment motion. Figure 6 (d) The glass transition temperatures of pure PUE, PUE / BOX8, and PUE / DMPB8 are 42.73℃, 21.95℃, and -3.95℃, respectively. Compared to pure PUE, the addition of BOX and DMPB significantly shifts the main peak of the loss factor towards lower temperatures. This further indicates that the incorporation of DMPB broadens the free volume between chain segments, and the molecular chains still possess good mobility even at low temperatures. Meanwhile, the peak loss factor of PUE / DMPB8 is 0.656, higher than that of pure PUE and PUE / BOX8, meaning that this composite material has stronger energy dissipation capabilities in the main relaxation range.
[0075] Figure 6 (e) shows that the maximum loss modulus of PUE / DMPB8 is significantly higher than that of the other two material groups. This indicates that under external force, this composite material can dissipate mechanical energy through chain segment movement and internal friction, effectively alleviating local stress concentration. Figure 6 (f) It can be seen that the PUE / DMPB8 storage modulus is the highest in the low-temperature range, indicating that its initial glassy stiffness is stronger. When the temperature exceeds the glass transition temperature, the storage modulus of the material decreases. This characteristic allows the molecular chains to undergo significant deformation when the material is subjected to external impact, unlike rigid materials that will undergo brittle fracture, thus converting mechanical energy into heat energy.
[0076] (6) Waterproof performance The study conducted water resistance tests to evaluate the hydrolytic stability of the polyurethane elastomer matrix and the anti-exudation performance of the DMPB flame retardant, ensuring the long-term stable use of the composite material in humid environments (e.g., Figure 7 (As shown). First, the water contact angle of the polyurethane elastomer sample surface was tested, by... Figure 7 (a) It can be seen that the PUE / DMPB8 sample has the highest water contact angle, reaching 86.0°. This is because during the film formation process, the low surface energy benzene rings and alkyl groups contained in DMPB are enriched on the material surface, forming a hydrophobic protective layer that can resist the initial wetting of water.
[0077] After immersing the samples in water at 35℃ for 24 hours, the water absorption rate was tested. The water absorption rate of the pure polyurethane elastomer sample was 2.11%, while the water absorption rates of the PUE / BOX8 and PUE / DMPB8 samples were 2.90% and 5.60%, respectively (as shown in Table 4). After immersion and drying, the mass of all samples basically returned to the initial level. This indicates that although the polar groups in DMPB and the increased free volume inside the material facilitate water penetration, the covalent bond structure can maintain the chemical integrity of the material network and effectively prevent the leaching and loss of flame retardant components.
[0078] To further investigate the hydrolytic stability of polyurethane elastomer materials, pure PUE and its composites were immersed in deionized water at 35℃ for 24h and 48h, respectively. The samples were then removed, dried to constant weight at 60℃, and their mechanical and flame-retardant properties were subsequently tested. Figure 7 (c) to Figure 7 As shown in (e) and Table 5, the tensile strength and elongation at break of the polyurethane elastomer gradually decreased with increasing immersion time after water immersion. The PUE / BOX8 sample exhibited a relatively high retention rate of tensile strength, but its elongation at break decreased significantly, indicating that the molecular chain length shortened and the entanglement between molecular chains weakened after water immersion. In contrast, the PUE / DMPB8 sample retained 94.02% and 94.43% of its tensile strength and 102.99% and 109.22% of its elongation at break after immersion for 24 and 48 hours, respectively. This confirms that DMPB has excellent chemical bond strength and can significantly inhibit the hydrolytic breakage of polyurethane urethane groups.
[0079] The peel strength test results showed the same pattern of change. Figure 7 (f and Table 6). PUE / DMPB8 not only has the best initial average peel strength, but also maintains the highest peel strength and strength retention rate after immersion in water for 24h and 48h. This means that the PNB synergistic structure inside DMPB can act as an integral unit, constructing more stable covalent connection sites on the polyurethane elastomer molecular chain, while its main framework can effectively block hydrolysis.
[0080] Limiting oxygen index and UL-94 flame retardancy rating were tested on three groups of water-immersed samples. Figure 7 (g, 7h, Table 7). The limiting oxygen index values of all samples fluctuated little after immersion in water, but the limiting oxygen index of pure PUE and PUE / BOX8 samples was generally low, and neither type of sample met the UL-94 flame retardant rating standard. However, after immersion in water for 24h and 48h, the limiting oxygen index of PUE / DMPB8 samples remained at 32.8% and 32.6% respectively, and both tests met the UL-94 V-0 flame retardant rating, further demonstrating that DMPB has excellent anti-exudation ability in polyurethane matrix.
[0081] Combination Figure 7 (i) Summary of the water resistance mechanism of PUE / DMPB8: The benzene ring and alkyl structure in DMPB can reduce the initial wetting effect of water on the material surface. When water further penetrates into the material matrix, the cycloboroxane structure inside DMPB preferentially adsorbs water molecules, acting as a dynamic response site to interact with water molecules first, transferring the impact of water to the boronoxane dynamic structure. Under the action of water molecules, this structure undergoes a reversible dynamic change, reducing the probability of water molecules directly attacking the urethane structure of the polyurethane backbone. At the same time, the polar groups such as P=O, PN, and NH inside DMPB, coupled with the increased free volume of the material, accelerate water penetration. Most of the penetrated water is bound within the DMPB distribution area and will not continuously damage the hydrogen bonds of the hard segments of the polyurethane elastomer or the interface structure between the hard and soft segments.
[0082] Compared to PUE / BOX8, PUE / DMPB8, with its phosphoramide structure, aromatic framework, and multiple phosphorus, nitrogen, and boron active sites, constructs a more stable covalent anchoring system. The synergistic effect of these structures weakens the destructive impact of water molecules, and the internal network structure recovers well after drying, without structural shrinkage or decreased tensile properties. Furthermore, the covalent bond structure formed by DMPB effectively reduces the risk of migration, volatilization, and surface precipitation of flame-retardant components. In summary, the excellent water resistance of PUE / DMPB8 is not solely achieved through a hydrophobic barrier layer, but rather by leveraging DMPB to regulate the action pathways of water molecules.
[0083] Table 4. Water absorption and drying recovery rate of PUE and its composites
[0084] Note: a: Mass after drying at 60℃ for 48 hours; b: Mass after absorbing water at 35℃ for 24 hours.
[0085] Table 5 Tensile strength, elongation at break, and retention rate of PUE and its composite materials before and after water treatment
[0086] Note: a: tensile strength; b: tensile strength retention rate; c: elongation at break; d: elongation at break retention rate.
[0087] Table 6. Average peel strength and strength retention of PUE and its composite materials before and after water treatment.
[0088] Table 7. Limiting Oxygen Index, UL-94 Flame Retardancy Rating, and Retention of Various Indicators After Water Treatment
Claims
1. A method for preparing a flame-retardant and water-resistant polyether-type polyurethane elastomer, characterized in that, Includes the following steps: S1 Preparation of cycloboroxane intermediate: 3-APBA was dispersed in toluene, heated to 80-100℃ and refluxed with stirring for 12-14 h; after cooling to room temperature, the precipitate was collected by filtration, washed with toluene to remove residual reactants, and then dried under vacuum to obtain cycloboroxane intermediate BOX; S2 Preparation of reactive flame retardant: Dissolve BOX in DMF to obtain BOX solution; heat DMMP to 100-120℃, and add BOX solution dropwise to DMMP; after the addition is complete, raise the temperature to 160-170℃ and keep it at the temperature for 24-48h; after the reaction is complete, remove the solvent by rotary evaporation to obtain liquid product DMPB. Preparation of flame-retardant polyurethane elastomer S3: Dehydrated polyether polyol is treated at 110-120℃ for 2-3 hours under vacuum to remove residual moisture; after cooling to 50-60℃, isocyanate is added, followed by heating to 75-80℃ and holding for 2-3 hours to obtain isocyanate-terminated polyurethane prepolymer; DMPB is dissolved in DMF and added to the prepolymer and stirred, followed by TMP, and the resulting mixture is stirred before casting; after casting, the sample is degassed under vacuum to remove entrained air bubbles and solvent, and cured to obtain flame-retardant polyurethane elastomer.
2. The method for preparing the flame-retardant and water-resistant polyether-type polyurethane elastomer as described in claim 1, characterized in that, In step S1, the vacuum drying temperature is 80-110℃ and the time is 6-12h.
3. The method for preparing the flame-retardant and water-resistant polyether-type polyurethane elastomer as described in claim 1, characterized in that, In step S2, the concentration of the BOX solution is 0.4-0.93 mol / L.
4. The method for preparing the flame-retardant and water-resistant polyether-type polyurethane elastomer as described in claim 1, characterized in that, In step S2, the mass ratio of BOX to DMMP is 1:(3.3-3.8).
5. The method for preparing the flame-retardant and water-resistant polyether-type polyurethane elastomer as described in claim 1, characterized in that, In step S2, the pressure during rotary evaporation is -0.09 to -1 MPa.
6. The method for preparing the flame-retardant and water-resistant polyether-type polyurethane elastomer as described in claim 1, characterized in that, In step S3, the polyether polyol is PPG-2000 and the isocyanate is MDI-50, with a mass ratio of 1:(0.65-0.7).
7. The method for preparing the flame-retardant and water-resistant polyether-type polyurethane elastomer as described in claim 1, characterized in that, In step S3, the mass ratio of DMPB, TMP and polyether polyol is 1:(0.9-2.3):(6-13.5).
8. The method for preparing the flame-retardant and water-resistant polyether-type polyurethane elastomer as described in claim 1, characterized in that, In step S3, the curing temperature is 80-100℃ and the time is 12-24h.
9. A flame-retardant and water-resistant polyether-type polyurethane elastomer, characterized in that, It is prepared by the preparation method of flame-retardant and water-resistant polyether polyurethane elastomer as described in any one of claims 1-8.